Investigating the Efficacy of Focused and Unfocused Corrective Feedback on the Accurate Use of Prepositions in Written Work - Asiah, Kassim; Lee, Luan Ng (Canadian Center of Science and Education, 2014)
This paper discusses findings from a study investigating feedback efficacy on the accurate use of prepositions by ESL learners in written work over a period of 12 weeks. The study involved two treatment groups and a control group comparing the differential effects of the focused indirect with the unfocused indirect corrective feedback on the uptake and retention measured from the pretest, immediate and delayed posttests. The study also analysed the language-related episodes (LREs) occurring in the collaborative dialogue during the treatment sessions to identify the factors affecting uptake and retention of the corrective feedback in subsequent writing tasks. Findings revealed that both treatment groups outperformed the control group in the posttests, but, there was no significant difference between the unfocused and focused corrective feedback groups. Evidence from the LREs analysis suggests that extensive engagement in all the three functions of the Swain (2005) output hypothesis: noticing, hypothesis testing and metalinguistic, during the collaborative dialogue contribute toward the enhancement of uptake and retention. Since both correction types were equally facilitative in increasing accuracy of preposition usage, teachers may consider using them accordingly in writing tasks.